Koncepcje edukacji w dyskursie posthumanistycznym - Kamińska, Małgorzata (Rocznik Pedagogiczny, 2022)
In the post-humanistic discourse, the concepts of humanity, subjectivity, civilization and knowledge change (expand) their meaning. The scale of development of digital technologies, algorithmization and automation of people’s lives also plays a significant role. Today we know that the Anthropocene epoch brought (and continues to bring) more harm than benefit in the relations between man and nature, man and man, subject and object. In addition, the pandemic crisis has sharpened the picture of problems and challenges that humanity should face. Following this, the concepts of traditional education are also being revised. The text attempts to identify educational concepts that in the near future may change the humanistic visions of education and upbringing. It is a reflection on the potential of the post-humanis- tic understanding of education in the era of civilization crisis and global threats.